Leaving no one behind: Party clientelism in social welfare in Serbia - Vuković Danilo; Stefanović Marija (Anali Pravnog Fakulteta u Beogradu)
This article analyzes the functioning of party patronage and clientelism in the centers for social work. Building on previous research, based on qualitative research conducted in 2023 in Serbia, we examine parasitic relations of informal and formal institutions and their ability to nihilate the legal system and create a parallel or dual normative system. The initial step in institutional capture is party patronage and the deprofessionalization of public services. We further demonstrate how party cadre employed in public institutions create and reproduce clientelist networks and divert the working of the institutions. Finally, most public sector employees quietly comply with the expectations to work in the network's interest, creating a new culture of fear and professional and civic passivity. We argue that informal institutions of clientelism parasitize formal institutions and that capturing institutions and society transforms the internal norms of clientelist networks into social norms, creating a backbone of normative dualism.